2016
DOI: 10.1038/labinvest.2016.65
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia-stimulated cardiac fibroblast production of IL-6 promotes myocardial fibrosis via the TGF-β1 signaling pathway

Abstract: Interlukin-6 (IL-6) is a multifunctional cytokine produced by several cell types that has a role in fibrosis. Fibroblasts (FBs) maintain this underlying pathogenic change through regulation of IL-6 production; however, its potential functional role in regulating surrounding cellular structural changes during ischemic myocardial remodeling remains unexplored. Here, we generated FBs, cardiomyocytes (CMs), and blood vascular endothelial cells (ECs) from the ventricles of neonatal rats. IL-6 was then overexpressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 32 publications
1
55
0
4
Order By: Relevance
“…Trx-1 also has antiapoptotic and growth stimulatory functions through interactions with apoptosis signal regulation kinase-1 (Saitoh et al, 1998) and hypoxia inducible factor-1 alpha (Welsh et al, 2002). In this study, Trx-1 overexpression also increased levels of the apoptosis-associated proteins caspase 3 and decreased expression of the antiapoptosis factor Bcl2, which has previously been described in an in vitro model of hypoxia-induced fibrosis (Wang et al, 2016).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Trx-1 also has antiapoptotic and growth stimulatory functions through interactions with apoptosis signal regulation kinase-1 (Saitoh et al, 1998) and hypoxia inducible factor-1 alpha (Welsh et al, 2002). In this study, Trx-1 overexpression also increased levels of the apoptosis-associated proteins caspase 3 and decreased expression of the antiapoptosis factor Bcl2, which has previously been described in an in vitro model of hypoxia-induced fibrosis (Wang et al, 2016).…”
Section: Discussionsupporting
confidence: 79%
“…Here, Trx-1 overexpression prevented thickening of the dermis in an SSc mouse model, suggesting that Trx-1 can also protect against SSc, possibly by inhibiting ROS production. Enhanced TGF-b signaling has been shown to promote fibrosis (Wang et al, 2016); therefore, Trx-1 may exert its antifibrotic effect through TGF-b.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-6-deficient (IL-6(−/−)) mice had relatively attenuated fibrotic changes following bleomycin treatment in comparison to the wild type controls [8]. Recent studies showed that the IL-6 can also promote fibrosis by driving chronic inflammation [5] and by activating the TGFβ pathway [9,10], which is the most potent profibrotic cytokine known [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The induction of IL-6 secretion by hypoxic stress per se remains debated; lack of or moderate inductions of IL-6 protein secretion by hypoxic stress have been described in other cellular models; a significant IL-6 induction may require prolonged hypoxia or reoxygenation steps. Hypoxic stress was found associated with an increased expression of IL-6 mRNA, as shown in fibroblasts, vascular smooth cells, endothelial cells, astrocytes or cardiac myocytes, and TECs, after a brief or a prolonged hypoxic challenge [40][41][42][43][44]. Mechanisms linking signaling pathways activated by hypoxia to the increased expression of IL-6 mRNA remain to be fully understood; however, some cues may be brought by transcription studies that show increased transcription of the IL-6 gene upon hypoxic stress [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%